Prevalence and Risk Factors for Developing UTI in Women - Gaybullaev, O.A.; Abdurizaev, A.A.; Gaybullaev, A.A. (International Journal of Psychosocial Rehabilitation, 2020)
This article is written with the aim of presenting the results of a clinical trial, diagnosis and treatment of UTI in women. Characteristics of a common causative agent of uncomplicated UTI such as Escherichia coli, detected in about 80% of cases, and Staphylococcus saprophyticus, which causes the development of another 15% of cases, are given. In particular, the causes of complicated UTI were identified, the reason for their development is often bacteria that are extremely rare in uncomplicated forms, such as Pseudomonas aeruginosa and Proteus mirabilis, as well as group B streptococci.